2019
DOI: 10.1038/s41598-019-43015-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of heavy metal pollution using ion-exchange resin sachets and micro-XRF core-scanning

Abstract: Conventional pollution monitoring strategies for heavy metals are often costly and unpractical. Innovative sampling and analytical approaches are therefore needed to efficiently monitor large areas. This study presents a novel, simple, fast, and inexpensive method to monitor heavy metal pollution that uses cation-exchange resin sachets and the micro-XRF core-scanning technique (XRF-CS). The resin passive samplers act as concentrators of cationic species and can be readily deployed spatially and temporally to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The concentration of the adsorbed heavy metals on the time-lapse capsules could also be rapidly determined by the nondestructive X-ray uorescence core-scanning (XRF-CS) technique. 3,11 According to the results reported by Huang et al, 3 the concentrations of heavy metals determined by the XRF-CS (the increase on the resin) and the conventional analytical method (the reduction in water) exhibited excellent correlations (R 2 > 0.97) even at a short scanning time (<1 s). By doing so, one could identify the potential hot spots of illegal discharge in situ and then keep deploying more time-lapse capsules upstream until the discharge point of the industry is located.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The concentration of the adsorbed heavy metals on the time-lapse capsules could also be rapidly determined by the nondestructive X-ray uorescence core-scanning (XRF-CS) technique. 3,11 According to the results reported by Huang et al, 3 the concentrations of heavy metals determined by the XRF-CS (the increase on the resin) and the conventional analytical method (the reduction in water) exhibited excellent correlations (R 2 > 0.97) even at a short scanning time (<1 s). By doing so, one could identify the potential hot spots of illegal discharge in situ and then keep deploying more time-lapse capsules upstream until the discharge point of the industry is located.…”
Section: Introductionmentioning
confidence: 77%
“…The detailed procedure for the preparation of time-lapse capsules can be found in our previous studies. 3,11…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Itrax XRF-CS, which is a unique multi-function scanner for core examination, is commonly used for geological research, and it can detect the element profiles of sediment core. Raychaudhuri et al [50] used the Itrax XRF-CS to analyze the exposure time of resins in laboratory and field survey. Their results showed that resin samples can be measured in approximately 20 s and identified pollution hot spots in a rapid way.…”
Section: X-ray Fluorescence (Xrf) Spectrometrymentioning
confidence: 99%
“…In order to overcome this critical issue, several innovative inspection technologies, such as time-lapse capsules [7,8], have been developed and deployed in the field tests for identifying the patterns of the heavy metals from the illegal discharge. Apart from the innovative inspection, the integration of continuous automatic sampling techniques and cloud technologies was imperative to provide the real-time monitoring for identifying the sources of pollution and improving the irrigation water quality management.…”
Section: Introductionmentioning
confidence: 99%